Mechanisms of bacterial detoxification of Cr(VI) from industrial wastewater in the presence of industrial effluent as potential energy source - Ahmad, Wan Azlina; Shahir, Shafinaz; Zakaria, Zainul Akmar (Faculty of Science, 2009)
Chromium (Cr), especially Cr(VI) is of particular environmental concern owing to its high solubility, bioavailability and toxicity. The reduction of Cr(VI) to innocuous Cr(III) is an important step in the remediation of Cr(VI)-contaminated environments. The understanding of how microorganisms resist metals can provide insight into strategies for their detoxification or removal from the environment. The present investigation was undertaken to study the Cr(VI) resistance mechanisms by Acinetobacter haemolyticus, a strain isolated from Cr(VI)-containing textile wastewater. In preliminary studies, the strain was shown to be able to tolerate Cr(VI) concentrations of 30 and 90 mg L-1 in Luria-Bertani (LB) agar and broth respectively. The Cr(VI) reduction capacity of A. haemolyticus was found to be greater when grown in higher percentage of LB broth than minimal salts broth. The Cr(VI) reduction also increased with lower initial concentration of Cr(VI) added after 5 hours. The x-ray absorption fine structure (XAFS) analysis displayed the ability of the strain to reduce Cr(VI) to Cr(III) which was octahedrally coordinated to oxygen. The Cr(III) was most likely to form complexes with carboxyl (COO-) groups from the biomass based on Fourier-transform infrared (FTIR) analysis. The FTIR analysis also showed interactions of chromium with amino and hydroxyl groups. Field-emission scanning electron microscope (FESEM) showed that cells grown in the presence of Cr(VI) had a wrinkled appearance with a significant increase in size. No precipitates were found on the cell surface. However, precipitates were observed in the cytoplasmic region of the cells via transmission electron microscope (TEM) analysis, suggesting the transport of Cr(VI) into the cytoplasm and intracellular Cr(VI) reduction. Intracellular reduction of Cr(VI) was supported by a reductase test using soluble crude cell - free extracts. The specific reductase activity obtained was 0.52 Î¼g Cr(VI) reduced per mg of protein an hour at pH 7.2 and 37 ËšC. In plasmid screenings, the strain was found to harbor a plasmid of about 12 kb. The findings showed that Cr(VI) resistance mechanisms of A. haemolyticus include the reduction of Cr(VI) to Cr(III), and intra- and extracellular sequestration of chromium.